The bibliometric review on convective heat transfer of nanofluid - Mohd Kasim, Abdul Rahman; Fauzi, Farahanie; Waini, Iskandar; Mohd Kanafiah, Siti Farah Haryatie; Tijani, Yusuf Olatunji (Penerbit Akademia Baru, 2024)
Since convective heat transfer of nanofluids research has advanced significantly, it is helpful to have a brief overview of what has been done, who has been engaged, and how much they have contributed in order to choose our future course of action. Therefore, the objective of this study is to do a bibliometric analysis of the convective heat transfer of nanofluids. The reviewed articles were extracted using the advanced documents search function in SCOPUS database. The search keywords employed in this investigation encompass “convective heat transfer” and “nanofluids”. The first set of documents searched are sorted by article type and year, from 2002 to 2023. VOSviewer is then used to conduct the bibliometric analysis. Findings discovered that current and future research is moving towards investigating hybrid nanofluids flowing through microchannels and porous media, along with the influence of external factors such as pumping power.